PEMETAAN POTENSI KERUSAKAN TANAH PADA KAWASAN BUDIDAYA DI KECAMATAN TERIAK KABUPATEN BENGKAYANG - Apriharyandi, Andre; Nusantara, Rossie Wiedya; Sulakhudin (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
In the context of cultivation areas, soil plays a highly strategic role because these areas are specifically designated for activities such as agriculture, plantations, fisheries, and animal husbandry. High-intensity use of soil in cultivation areas carries the risk of potential soil degradation if not managed wisely. The initial step in addressing soil degradation is to conduct an inventory of the potential for soil degradation in a given region. The determination of potential soil degradation refers to the guidelines of the Ministry of Environment (2009), using overlay, scoring, and weighting methods. Overall, the Teriak Subdistrict area has a low to moderate potential for soil degradation. In cultivation areas, the largest area with a low level of degradation is designated for horticultural agriculture (843.81 hectares), while the largest area with a moderate level of degradation is dominated by plantation use (10,026.79 hectares) and food crop agriculture (9,241.52 hectares). Factors that most influence the highest soil degradation potential scores include topography with steep slopes (26–40%) and dryland agricultural land use.